Integrated Waste Heat Recovery System using Thermoelectric Generator (TEG) - N. Manalo, Josias; Sean C. Maratas, Edward; O. Narvaza, Raymond; C. Pacis, Michael; Vincent M. Santiago, Ronald (International Journal of Engineering and Technology, 2018)
To date, everyone is engaged in renewable energy. Some of the renewable sources are solar, hydro, wind and geothermal energy. An alternative source is waste thermal energy. This paper focuses on recovering waste heat of vehicles to produce electrical energy for charging purposes. The waste heat of vehicles was recovered through thermoelectric effect. According to the study about Seebeck and Peltier effects which was conducted by Pnakovich, if two junctions are made between two different conductive metals and are held at different temperatures, voltage will be created from a temperature difference between these junctions. The resulting electrical energy will be used in charging the independent battery of the vehicle. The researchers decided to integrate or combine the output voltage through the heat recovered from the exhaust pipe and radiator. The thermoelectric modules were placed in an aluminumcha plate, a group of modules is installed on top of a customize muffler which is connected in the exhaust pipe while the other group of modules is placed below the radiator. The exhaust pipe and radiator of the vehicle serves as the heat source while the circulating water is the cold side. The higher temperature difference, the higher voltage will be generated. The microcontroller has two components which are to transmit and receive part. The microcontroller measures voltage, current, temperature from hot and cold side and its temperature difference, then the data except the current is transmitted into the LCD display using Bluetooth. The combined output from the group of thermoelectric modules must have at least 12 volts to charge the independent battery. The researchers conducted an experiment in different road conditions like traveling uphill, downhill, straight and traffic situation. The maximum generated voltage is 16.22 V when conducted at uphill and the current is 12.973 mA. The maximum temperature from the hot side is 325.9 degrees Celsius. The lowest temperature from the cold side is 23.4 degrees Celsius.Â